Association of Health Insurance Payer Type and Outcomes After Durable Left Ventricular Assist Device Implantation: An Analysis of the STS-INTERMACS Registry. (May 2021) - Khatana, Sameed Ahmed M.; Hanff, Thomas C.; Nathan, Ashwin S.; Dayoub, Elias J.; Grandin, E. Wilson; Rame, J. Eduardo; Fanaroff, Alexander C.; Giri, Jay; Groeneveld, Peter W.
Abstract : Background: Due to the high cost of left ventricular assist device (LVAD) therapy, payer type may be an important factor in determining eligibility. How payer type influences outcomes after LVAD implantation is unclear. We, therefore, aimed to study the association of health insurance payer type with outcomes after durable LVAD implantation. Methods: Using STS-INTERMACS (Society of Thoracic Surgeons-Interagency Registry for Mechanically Assisted Circulatory Support), we studied nonelderly adults receiving a durable LVAD from 2016 to 2018 and compared all-cause mortality and postindex hospitalization adverse event episode rate by payer type. Multivariable Fine-Gray and generalized linear models were used to compare the outcomes. Results: Of the 3251 patients included, 26.0% had Medicaid, 24.9% had Medicare alone, and 49.1% had commercial insurance. Compared with commercially insured patients, mortality did not differ for patients with Medicaid (subdistribution hazard ratio, 1.00 [95% CI, 0.75–1.34], P =0.99) or Medicare (subdistribution hazard ratio, 1.09 [95% CI, 0.84–1.41], P =0.52). Medicaid was associated with a significantly lower adjusted incidence rate (incidence rate ratio, 0.88 [95% CI, 0.78–0.99], P =0.041), and Medicare was associated with a significantly higher adjusted incidence rate (incidence rate ratio, 1.16 [95% CI, 1.03–1.30], P =0.011) of adverse event episodes compared with commercially insured patients. Conclusions: All-cause mortality after durable LVAD implantation did not differ significantly by payer type. Payer type was associated with the rate of adverse events, with Medicaid associated with a significantly lower rate, and Medicare with a significantly higher rate of adverse event episodes compared with commercially insured patients. Abstract : Supplemental Digital Content is available in the text.